La actualidad del principio de equilibrio económico y financiero en “contratos modernos”: 20 años de la emisión del voto 6432-98 de la sala constitucional - López Jiménez, Enrique (2020)
In 2018, 20 years have passed since the issue of Ruling 643298 of the Constitutional Chamber of the Supreme Court of Justice of Costa Rica. This ruling recognizes the right to economic equilibrium in government contracting. After 20 years, the reality of Public Administrations has changed. The public work contract is no longer the norm and, on the contrary, we find different contractual types classified as “modern” (PPA, BOT, EPC, Turnkey). Recent rulings of the Contentious Administrative Court have examined the right to economic and financial equilibrium in these contracts. But, is it still possible to talk about the right to economic and financial equilibrium of government contracts in Costa Rica?